Canada : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2008)
The paper presents Canada's report on the Observance of Standards and Codes on the Financial Action Task Force (FATF) recommendations for Anti-Money Laundering (AML) and Combating the Financing of Terrorism (CFT). Canada has strengthened its overall AML/CFT regime since its last FATF mutual evaluation (1997) by implementing a number of changes both in terms of statutory amendments and structural changes. The most important developments have been the enactment of the Proceeds of Crime and Terrorist Financing Act and the creation of the Canadian Financial Intelligence Unit in 2000.